Metallic and semiconducting nanoparticles in LCs - Sharma, Anshul; Urbanski, Martin; Mori, Taizo; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Series in Soft Condensed Matter)

Influence of Proton and Salt Concentration on the Chromonic Liquid Crystal Phase Diagram of Disodium Cromoglycate Solutions: Prospects and Limitations of a Host for DNA Nanostructures - Zhang, Bingru; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Alignment and Graphene-Assisted Decoration of Lyotropic Chromonic Liquid Crystals Containing DNA Origami Nanostructures - Martens, Kevin; Funck, Timon; Kempter, Susanne; Roller, Eva-Maria; Liedl, Tim; Blaschke, Benno M.; Knecht, Peter; Garrido, José Antonio; Zhang, Bingru; Kitzerow, Heinz-Siegfried (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Integral representation and sharp asymptotic results for some Heckman-Opdam hypergeometric functions of type BC - Rösler, Margit; Voit, Michael (Transactions of the American Mathematical Society)

A multivariate version of the disk convolution - Rösler, Margit; Voit, Michael (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Time-Resolved Mueller Matrix Measurement and Polarization Scrambler Characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Erklärungsfaktoren für Einstellungen von Schülerinnen und Schülern im Grundschulalter gegenüber Kindern mit sonderpädagogischem Förderbedarf – Ergebnisse aus einer empirischen Studie. Vortrag auf der 51. Arbeitstagung der Dozierenden der Sonderpädagogik in deutschsprachigen Ländern „Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik“ - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

Leistungsrückmeldungen im Zusammenhang mit Leseleistungen, Selbstwirksamkeitsüberzeugungen und Kausalattributionen bei Kindern im dritten und vierten Grundschuljahr. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Ort, Margarita; Hellmich, Frank

Prädiktoren für Einstellungen und Motivation bei Studentinnen und Studenten des Lehramts an Grundschulen in Bezug auf den inklusiven Unterricht. Vortrag auf der 51. Arbeitstagung der Dozierenden der Sonderpädagogik in deutschsprachigen Ländern „Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik“ - Görel, Gamze; Hellmich, Frank

Engineering the Frequency Spectrum of Bright Squeezed Vacuum via Group Velocity Dispersion in an SU(1,1) Interferometer - Lemieux, Samuel; Manceau, Mathieu; Sharapova, Polina; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Physical Review Letters)
Keywords: General Physics and Astronomy

Tunable optical parametric generator based on the pump spatial walk-off - Cavanna, Andrea; Just, Felix; Sharapova, Polina; Taheri, Michael; Leuchs, Gerd; Chekhova, Maria V. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Förderung inklusiven Lernens im naturwissenschaftlich-technischen Sachunterricht der Grundschule. Vortrag auf der 4. Jahrestagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Blumberg, Eva; Fromme, Theresa; Hellmich, Frank

Zur Feinstaubabscheidung aus Holzfeuerungsanlagen mit precoatierten Oberflächenfiltern - Schiller, Sascha

Tailoring the textural properties of hierarchical porous carbons using deep eutectic solvents - Lopez Salas, Nieves; Carriazo, D.; Gutiérrez, M. C.; Ferrer, M. L.; Ania, C. O.; Rubio, F.; Tamayo, A.; Fierro, J. L. G.; del Monte, F. (Journal of Materials Chemistry A)
DESs containing resorcinol, urea and choline chloride allow the preparation of monolithic carbons with bicontinuous porous structures, the pore dimension of which can be easily tailored by the molar ratio of the components at the original DES.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Kinder mit Lernschwierigkeiten in der Grundschule - Miller, Susanne; Kottmann, Brigitte (Differenz - Ungleichheit - Erziehungswissenschaft)

"Und dann war das auch noch so ein kleines, zartes Persönchen": Grundschullehrkräfte im Entscheidungsdilemma zwischen Fördern und Selektieren - Miller, Susanne; Kottmann, Brigitte (Diagnostik im Kontext inklusive Bildung)

Selektion inklusive?! Widersprüche bei der umsetzung von Inklusion in der Schule - Kottmann, Brigitte; Miller, Susanne (Empirische Forschung im Kontext Schule)

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

In-lab ALOHA mid-infrared up-conversion interferometer with high fringe contrast @λ = 3.39 μm - Szemendera, L.; Darré, P.; Baudoin, R.; Grossard, L.; Delage, L.; Herrmann, Harald; Silberhorn, Christine; Reynaud, F. (Monthly Notices of the Royal Astronomical Society)
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy

Bayesian Information Criterion for Source Enumeration in Large-Scale Adaptive Antenna Array - Huang, Lei; Xiao, Yu-Hang; Liu, Kefei; So, Hing Cheung; Zhang, Jian-Kang (IEEE Transactions on Vehicular Technology)

Shrinkage of covariance matrices for linear signal estimation using cross-validation - Tong, Jun; Schreier, Peter J.; Guo, Qinghua; Tong, S.; Xi, Jiangtao; Yu, Y. (IEEE Trans.\ Signal\ Process.)

DOA parameter estimation with 1-bit quantization - Bounds, methods and the exponential replacement - Stein, Manuel; Barbé, Kurt; Nossek, Josef A. (Proc.\ ITG Int.\ Work. Smart Ant.)

Asymptotic performance analysis for $1$-bit Bayesian smoothing - Zhang, Lin; Stein, Manuel; Nossek, Josef A. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Performance analysis for pilot-based $1$-bit channel estimation with unknown quantization threshold - Stein, Manuel; Bar, Shahar; Nossek, Josef A.; Tabrikian, Joseph (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Choosing the diagonal loading factor for linear signal estimation using cross validation - Tong, Jun; Guo, Qinghua; Xi, Jiangtao; Yu, Y.; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Adaptive visual sort and summary of micrographic images of nanoparticles for forensic analysis - Jurrus, Elizabeth; Hodas, Nathan; Baker, Nathan; Marrinan, Tim; Hoover, Mark D (Technologies for Homeland Security (HST), 2016 IEEE Symposium on)

Accurate Asymptotic Analysis for Johns Test in Multichannel Signal Detection - Xiao, Y-.H.; Huang, L.; Xie, J.; H. C. So, and (Proc. IEEE Int. Conf. Acoust., Speech, Signal Process. (ICASSP))

Canonical correlation analysis of high-dimensional data with very small sample support - Song, Yang; Schreier, Peter J.; Ramírez, David; Hasija, Tanuj (Signal Process.)

Detecting the dimension of the subspace correlated across multiple data sets in the sample poor regime - Hasija, Tanuj; Song, Yang; Schreier, Peter J.; Ramírez, David (Proc.\ IEEE Work.\ Stat.\ Signal Process.)

Bootstrap-based detection of the number of signals correlated across multiple data sets - Hasija, Tanuj; Song, Yang; Schreier, Peter J.; Ramírez, David (Proc.\ Asilomar Conf.\ Signals\ Syst. Computers)

Determining the number of signals correlated across multiple data sets for small sample support - Song, Yang; Hasija, Tanuj; Schreier, Peter J.; Ramírez, David (Proc.\ Eur.\ Signal Process.\ Conf.)

Reflexionen des Technischen zwischen Überleben und gutem Leben - Alpsancar, Suzana (Jahrbuch Technikphilosophie 2016. List und Tod)

Natur - Alpsancar, Suzana (Professionell Ethik und Philosophie unterrichten: Ein Arbeitsbuch)

Pollution Control Meets Sustainability: Structure-Activity Studies on New Iron Oxide-Based CO Oxidation Catalysts - Schoch, Roland; Bauer, Matthias (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Interkorporalität - Haller, Melanie; Klein, Gabriele; Meuser, Michael; Gugutzer (Hg.), Robert (Handbuch Körpersoziologie. Körpersoziologische Grundbegriffe und theoretische Perspektiven, Wiesbaden 2016.)

Salsa - Hartmann, Annette; Woitas, Monika; Haller, Melanie (Das große Tanzlexikon. Personen, Werke, Tanzkulturen, Epochen, Laaber: Laaber 2016, S. 530-531.)

Swing - Haller, Melanie; Hartmann, Annette; Woitas, Monika (Das große Tanzlexikon. Personen, Werke, Tanzkulturen, Epochen, Laaber: Laaber 2016.)

Implications of Guanidine Substitution on Copper Complexes as Entatic‐State Models - Hoffmann, Alexander; Stanek, Julia; Dicke, Benjamin; Peters, Laurens; Grimm‐Lebsanft, Benjamin; Wetzel, Alina; Jesser, Anton; Bauer, Matthias; Gnida, Manuel; Meyer‐Klaucke, Wolfram; Rübhausen, Michael; Herres‐Pawlis, Sonja (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

Molecular dynamics and reverse Monte Carlo modeling of scheelite-type AWO4(A = Ca, Sr, Ba) WL3-edge EXAFS spectra - Kalinko, Aleksandr; Bauer, Matthias; Timoshenko, Janis; Kuzmin, Alexei (Physica Scripta)
Keywords: Condensed Matter Physics; Mathematical Physics; Atomic and Molecular Physics; and Optics

Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.

Integrative Verknüpfung von Studium und Praxis am Leuphana College. - Hellmann, Karina; Teigeler, Mareike; Seifert, Andreas (Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.)

“Und sie bewegt sich doch!” – Wie spezifische Lerngelegenheiten die bildungswissenschaftlichen Kompetenzen von Lehramtsstudierenden fördern können. - Plöger, Wilfried; Scholl, Daniel; Seifert, Andreas (Zeitschrift für Pädagogik)

Universitäre Bildung und Hochschule im Wandel – das Beispiel Leuphana Universität Lüneburg. - Schütz, Julia; Seifert, Andreas; Gunkel, Marjaana (Das Hochschulwesen)

Smale-Scale-Assessments in den Bildungswissenschaften. - Lüders, Manfred; Seifert, Andreas (Lehrerbildung auf dem Prüfstand)

Preschoolers’ engagement in social interaction with an autonomous robotic system. - Lücking, Philipp; Rohlfing, Katharina; Wrede, Britta; Schilling, Malte (Proceedings of the IEEE ICDL-EpiRob 2016)

Vocal interactions at the dawn of communication: The emergence of mutuality and complementarity in mother-infant interaction. - Leonardi, Giuseppe; Nomikou, Iris; Rohlfing, Katharina; Rączaszek-Leonardi, Joanna (Proceedings of the IEEE ICDL-EpiRob 2016)

Pragmatic Frames for Teaching and Learning in Human–Robot Interaction: Review and Challenges - Vollmer, Anna-Lisa; Wrede, Britta; Rohlfing, Katharina; Oudeyer, Pierre-Yves (Frontiers in Neurorobotics)

Language meddles with infants‘ processing of observed actions - Sciutti, Alessandra; Lohan, Katrin Solveig; Gredebäck, Gustaf; Koch, Benjamin; Rohlfing, Katharina (Frontiers in Robotics and AI)

Language—at all times. Action and interaction as contexts for enriching representations. - Nomikou, Iris; Malte, Schilling; Heller, Vivien; Rohlfing, Katharina (Interaction Studies)